The endophytic microbiota of Citrus limon is transmitted from seed to shoot highlighting differences of bacterial and fungal community structures - Faddetta, Teresa; Abbate, Loredana; Alibrandi, Pasquale; Arancio, Walter; Siino, Davide; Strati, Francesco; De Filippo, Carlotta; Fatta Del Bosco, Sergio; Carimi, Francesco; Puglia, Anna Maria; Cardinale, Massimiliano; Gallo, Giuseppe; et al. (Scientific reports, 2021)
Citrus limon (L.) Burm. F. is an important evergreen fruit crop whose rhizosphere and phyllosphere microbiota  have been characterized, while seed microbiota is still unknown. Bacterial and fungal endophytes were isolated from C. limon surface-sterilized seeds. The isolated fungi—belonging to Aspergillus , Quambalaria and Bjerkandera genera—and bacteria—belonging to Staphylococcus genus—were characterized for indoleacetic acid production and phosphate solubilization. Next Generation Sequencing based approaches were then used to characterize the endophytic bacterial and fungal microbiota structures of surface-sterilized C. limon seeds and of shoots obtained under aseptic conditions from in vitro growing seedlings regenerated from surface-sterilized seeds. This analysis highlighted that Cutibacterium and Acinetobacter were the most abundant bacterial genera in both seeds and shoots, while Cladosporium and Debaryomyces were the most abundant fungal genera in seeds and shoots, respectively. The localization of bacterial endophytes in seed and shoot tissues was revealed by Fluorescence In Situ Hybridization coupled with Confocal Laser Scanning Microscopy revealing vascular bundle colonization. Thus, these results highlighted for the first time the structures of endophytic microbiota of C. limon seeds and the transmission to shoots, corroborating the idea of a vertical transmission of plant microbiota and suggesting its crucial role in seed germination and plant development.